Influence of preparation design and spacing parameters on the risk of chipping of crowns made with Cerec Bluecam before cementation. Issue 1 (January 2019) - Arena, A.; Baldissara, P.; Ciocca, L.; Scotti, R.; Monaco, C.
Abstract: Purpose: To evaluate the influence of the preparation design and spacing parameters on the risk of chipping of crowns made by CEREC Bluecam before cementation. Methods: A knife-edge preparation and a chamfer preparation were made on upper premolars. The teeth were scanned and two Co–Cr alloy replicas were made. Fifteen full crowns were manufactured for four groups using CEREC. The groups differed in type of preparation (knife-edge (KE) or chamfer (CHA)) and spacing parameters: spacer (0 or 150 μm), marginal adhesive gap (10 or 50 or 150 μm) and margin thickness (0 or 300 μm). The four groups were: CHA 150 (spacer)- 50 (marginal adhesive gap)- 0 (margin thickness), KE 150-50-0, KE 150-50-300 and KE 150-150-300. The crowns were loaded before cementation by using an Instron machine to simulate the masticatory load applied during a trial. Differences in means were compared using two-way ANOVA and a post-hoc test (Tukey Test). The level of significance was set at P = 0.05. Results: The fracture values, ordered from least to most resistant, were: KE 150-50-300 group, CHA 150-50-0 group, KE 150-50-0 group and KE 150-150-300 group. Two-way ANOVA revealed statistically significant differences between pairs of means (p < 0.05). Tukey's test showed that restorations of the KE 150-150-300 group can withstand a load significantly higher than that of other groups (p < 0.01). In this group, the failures were mostly minor chippings, while the other groups had mostly major chippings and fractures. Conclusions: Marginal adhesive gap can affect the trial of a full crown.